Determinants of sustainable behavior of firms and the consequences for customer satisfaction in hospitality. (August 2020) - Koch, Julia; Gerdt, Sven-Olaf; Schewe, Gerhard
Highlights: Unique data set connecting 974 hotels and 62, 766 customer satisfaction ratings. Novel measurement for sustainable behavior in hospitality. Innovativeness and sustainability attitude affect sustainable behavior. Implementation of sustainability measures depends on perceived advantages. Sustainable behavior of a firm has positive influence on customer satisfaction. Abstract: The literature on determinants of firm sustainable behavior and its effects on firm performance is rich. However, there are still important questions that lack definitive conclusions. One revolves around factors mediating the link between organizational determinants and firm sustainable behavior, which may still be regarded as a black box. Another stresses the impact of sustainable behavior on customer satisfaction. Using a sample of survey data from 974 small and medium-sized German hotels and 62, 766 independent reviews, this paper examines the links between innovativeness, managers' sustainability attitudes and firm sustainable behavior while taking into account perceived advantages of sustainable behavior as a mediator. Furthermore, the relationship between sustainable behavior and customer satisfaction is examined. A model is proposed and tested using structural equation modeling. The results confirm innovativeness and sustainability attitudes as determinants of sustainable behavior and perceived advantage as a mediator. Sustainable behavior shows a positive relation to customer satisfaction.